Methodological aspects of analysis of production costs of an industrial enterprise - O. Nesterenko; D. Khudiakova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Економіка)
The article is aimed at substantiating the methodological and organisational provisions of the analysis of costs of production of industrial products and developing recommendations for their use at industrial enterprises to improve their competitiveness. The article substantiates that in order to achieve efficiency and sustainability of production processes, it is important for industrial enterprises to systematically improve their cost management strategies. The theoretical provisions of cost analysis are substantiated. Approaches to organising and conducting cost analysis are systematised. A conceptual model for analysing production costs of an industrial enterprise has been developed, which includes the purpose of production cost analysis, its tasks, subjects, objects, principles, and methodological tools. The priority tasks of analysing the production costs of an industrial enterprise include: efficiency of the production process; determination of the cost of production; planning and control of budgets; and managerial decision-making. It is substantiated that the costs of production of industrial products are closely interrelated with some indicators of production efficiency, such as: indicators of profitability, liquidity, financial stability of enterprise. The analysis of production efficiency indicators is carried out on the example of the activities of the production and trading enterprise "PTC "ECMI" LLC. To analyse liquidity, the following indicators are used: total liquidity ratio, intermediate liquidity ratio and absolute liquidity ratio. The following indicators were used to analyse financial stability: autonomy ratio, financial stability ratio and financial risk ratio. To analyse profitability, the following indicators were used: return on assets (total), return on operating expenses, and return on sales. In order to assess changes in the structure of production costs, the article analyses the cost by cost elements, estimates their total volume, structural changes, and traces the dynamics of changes in the period from 2020 to 2022. The results of the analysis show that the company has optimised its costs, which has led to their reduction and increase in profitability. It is substantiated that an efficiently established analytical system enables the enterprise to timely monitor changes in production and prevent cost overruns, theft and inefficient use of raw materials, which is especially relevant during the period of military aggression in our country.